Perceptions and Lived Realities of Women’s Engagement in Environmental Conservation in Patriarchal Communities of Northern Uganda: A Qualitative Inquiry - Christine Ruth, Piloya; Abaho, Anne; Barakagira, Alex (International Journal of Global Health, 2026)
Background Women’s participation in environmental conservation within patriarchal societies is a critical factor for achieving sustainable development and improved community outcomes. Despite this importance, limited research has examined women’s perceptions of their roles and contributions to environmental conservation. The current study aimed to (1) explore women’s perceptions of their roles in environmental conservation within patriarchal structures, and (2) to document the effectiveness of strategies enhancing their participation. Methods This study followed a phenomenological design, using thematic data analysis. Information was gathered through semistructured interviews, focus group discussions (FGDs), and key informant interviews with technocrats, civil servants, local leaders, and NGO staff. The sample size of the study was 30 participants, obtained using the point of saturation principle. The focus group consisted of 24 participants and 06 Key Informants. The study tools were pretested with a small group before the main fieldwork. Participants were selected using purposive sampling. The size of the sample was guided by data saturation. Results The findings show that although women’s representation in local councils and environmental committees has grown due to the 30% quota requirement, their influence remains constrained by systemic barriers. Political interference undermines technical teams’ conservation efforts, while widespread community ignorance of environmental laws limits compliance. Weak enforcement and corruption, with leaders themselves implicated in destructive practices, further erode progress. Critically, inadequate financing such as subcounties allocating only 600,000 shillings for sensitization, leaves many activities unimplemented, forcing reliance on development partners. Conclusion The study concludes that sustainable environmental stewardship requires not only legal reforms and institutional accountability but also adequate financing and communitydriven strategies that amplify women’s voices and foster collective responsibility.
Keywords: women’s participation; environmental conservation; patriarchy; political interference; legal enforcement; inadequate financing; community sensitization; Gulu District